The impact of introducing the early warning scoring system and protocol on clinical outcomes in tertiary referral university hospital - Yuda Sutherasan (2019)
© 2018 Sutherasan et al. Purpose: The aim of this study was to evaluate the impact of a hospital protocol in response to patient deterioration in general wards, stratified using the national early warning score (NEWS), on primary patient outcomes of in-hospital mortality and percentage of patients transferred to the intensive care unit (ICU). Patients and methods: We conducted a prospective observational cohort study among adult medical patients admitted to a university hospital in Bangkok. A 4-month pre-protocol period (November 2015 to February 2016) was assigned to a control group and a protocol period (March 2016 to June 2016) was allocated to a protocol group. On admission, vital signs (respira-tory rate, pulse rate, systolic blood pressure, and temperature), oxygen saturation, presence of oxygen supplementation, and neurological status were used to calculate NEWS. Patients were categorized as low, moderate, or high risk based on the NEWS. During protocol period, when patients’ conditions are critical and they are at imminent risk, the NEWS detects the event and triggers a systematic response. The response enables closed monitoring and early treatment by expert physicians to rapidly stabilize and triage the patient to a location where services meet the patient’s needs. Primary outcomes were compared between the pre-protocol and protocol groups using historical controls for the intervention, which is the availability of NEWS to staff and an associated escalation pathway. Results: A total of 1,145 patients were included in the analysis: 564 patients in the pre-protocol group and 581 in the protocol group. The mean NEWS of patients at admission was higher in the protocol group than in the pre-protocol group (2.4±2.4 vs 1.77±2.158; P<0.001). There was no significant difference for in-hospital mortality and percentage of patients transferred to ICU between the groups. Among 95 (8.3%) patients at moderate risk, in-hospital mortality and ICU transfer percentage were lower in the protocol group than in the pre-protocol group (2.9 vs 15.4%; P=0.026; RR 0.188, 95% CI 0.037%–0.968% and 8.7 vs 26.9%; P=0.021; RR 0.322, 95% CI 0.12–0.87, respectively). Conclusion: Implementing the NEWS with the hospital protocol did not change the overall patient’s outcomes.